مدى فاعلية فرض القياس النقدي على القوائم المالية في ظل التغير في المستوى العام للأسعار - د. أسامة حسين محمد يوسف كير; د/ عبد الرحمن عبد الله الدين حبه عبد الله (White Nile Journal for Studies and Research, 2021)
The paper aimed at the relationship between the imposition of monetary measurement and the purchasing power prices of money, and its reflection on the expression of the sincerity of the values included in the items of the financial statements. The SPSS was used to analyze the study data. The study found many conclusions, among which the procedures for dealing with the impact of price change lead to the reliability of the financial statements. The amendment of the financial statements from the historical cost to the modified historical cost also contributes to addressing the problems of imposing monetary measurement. The study recommended several recommendations, the most important of which are. The need to pay attention to monetary measurement in light of inflation, which results in misleading information in the event that price changes are not taken into account, as well as the need to think seriously about measures to address the impact of price change to the credibility of financial statements by companies in the direction of applying the principles of inflation accounting for the purpose of determining sound profit and preserving the head The money invested and paying attention to the inflation index when preparing the financial statement forms and explaining their risk to the financial statements.